Validating eDNA measurements of the richness and abundance of anurans at a large scale. Issue 6 (7th April 2021) - Li, Wenhao; Hou, Xianglei; Xu, Chunxia; Qin, Mingshuo; Wang, Supen; Wei, Li; Wang, Yanping; Liu, Xuan; Li, Yiming
Abstract: In some situations, environmental DNA (eDNA) metabarcoding is a more accurate tool for measuring species richness of a taxon than conventional methods. Whether this tool can reliably estimate the abundance of a taxon remains unresolved. We examined the reliability of metabarcoding for measuring anuran diversity compared to a commonly used traditional line transect method (TLTM) through the replicate sampling of three visits across 71 waterbodies (ponds or reservoirs) in Liuheng, China. We also investigated the relative contributions of species‐specific characteristics and the physiochemical properties of a waterbody on the relative read count across species and waterbodies. We found that eDNA metabarcoding had a higher detection probability for each of seven anuran species found in the sampling region than TLTM. Furthermore, the relative read count estimated by metabarcoding was positively correlated with the density or relative density of individuals identified with the TLTM across waterbodies for every species. Species‐specific characteristics of anurans, such as density, relative density, body mass, biomass and relative biomass, accounted for substantial variations in the read count across species and waterbodies, while physiochemical factors, including pH, temperature, water volume, vegetation and elevation, had little effect on the read count. Our results based on robust sampling suggest that metabarcoding enables more reliable and efficient measurements of anuran occurrence at a large scale during a short‐term survey (within 15 days) than that obtained by the TLTM, and offers an alternative tool for quantifications of anuran abundance. Density or biomass is better and more reliable indicator of anuran abundance associated with read count than relative density or relative biomass. Abstract : The authors results based on robust sampling suggest that metabarcoding enables more reliable and efficient measurements of anuran occurrence at a large scale during a short‐term survey than that obtained by the traditional line transect method and offers an alternative tool for quantifications of anuran abundance. 摘要: 在某些情况下, 环境DNA (eDNA) 宏条形码 (metabarcoding) 技术在测量类群的物种丰富度上, 比传统的方法更准确。但它能否可靠地估计物种丰盛度, 还不清楚。 基于对中国六横岛71个水体 (池塘或水库) 三次重复抽样调查, 我们比较了eDNA宏条形码技术和传统的样线法 (traditional line transect method) 在监测蛙类多样性方面的可靠性, 并量化了物种特性和水体理化因素对水体中蛙类DNA浓度 (reads数) 的相对贡献。 我们在取样区域发现了7种蛙类物种, 包括入侵种北美牛蛙和6种当地种。eDNA宏条形码技术对每一种蛙类的探测概率均高于样线法。宏条形码技术测定的reads数与样线法估计的每种蛙的密度均呈显著正相关关系。蛙类的密度、相对密度、个体质量、生物量和相对生物量等物种特性, 对水体中的reads数有显著影响, 而水体的理化因素, 如pH值、温度、水体体积、植被盖度和海拔等, 对reads数影响不大。 基于大样本稳健抽样的结果表明, 在短期调查期间 (15天内), 宏条形码技术在调查大尺度蛙类分布上, 不但比样线法更可靠, 更经济有效, 而且能监测蛙类的丰盛度。密度或生物量等指标与reads数的相关性, 比相对密度或相对生物量等指标高, 是研究eDNA量化关系的可靠指标。